Envy and its objects - Alessandra Fussi (Humana.Mente: Journal of Philosophical Studies, 2019)
The paper critically discusses the thesis, originally put forth by Taylor (2006), that there is a (mostly benign) form of envy whose target is the good possessed by someone else. Section 2 analyzes the distinction between object-envy and state-envy, discusses the connection between object-envy and benign envy, and develops the ethical consequences that follow from the thesis that envy is never benign. Section 3 presents a thought experiment with five variations developed from the basic elements of object-envy: an agent, a good the agent desires but lacks, and a person who possesses the good. The variations generate emotions like longing, sadness, happiness for, admiration, covetousness, self-disappointment, but they do not generate envy. Section 4 concentrates on envious self-reproach and shows that its nature and genesis are different from the self-disappointment one may experience in other forms of self-assessment. Section 5 argues that the so-called sour-grape syndrome serves different goals when it is connected to a good one lacks and when it is connected to envious comparisons. Section 6 maintains that what looks like benign envy can be better understood as emulous admiration. In conclusion, the paper argues that object-envy is not a useful concept. The desired goods are not valued in themselves when a person feels envy. Rather, they are taken to signal the superior recognition enjoyed by someone else within the reference group that is currently deemed important by the agent.